2015
DOI: 10.1007/s00276-015-1529-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of bone and tissue morphological properties related to subacromial space geometry in a young, healthy male population

Abstract: The distributions of both morphological characteristics and occupation ratios indicate that individuals within this healthy, baseline population have a highly differential predisposition for subacromial tissue compression solely based on inherent morphological variation. This suggests that while mechanistic and/or age-related degenerative changes may contribute to SAIS and eventual rotator cuff pathology, intrinsic predisposing geometry should not be discounted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…The theory is that these measurement parameters show a reduced subacromial space. Chopp-Hurley et al reported that there is poor to moderate correlation between these morphological characteristics and subacromial width 36 . Balke et al showed in their studies that acromion morphology in degenerative RCTs differs from traumatic RCTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory is that these measurement parameters show a reduced subacromial space. Chopp-Hurley et al reported that there is poor to moderate correlation between these morphological characteristics and subacromial width 36 . Balke et al showed in their studies that acromion morphology in degenerative RCTs differs from traumatic RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Chopp-Hurley et al reported that there is poor to moderate correlation between these morphological characteristics and subacromial width. 36 Balke et al showed in their studies that acromion morphology in degenerative RCTs differs from traumatic RCTs. They reported that the subacromial space narrowed in degenerative but remained intact in traumatic tears.…”
Section: Discussionmentioning
confidence: 99%
“…The authors attributed this finding to age-related degeneration. Bone and soft tissue geometry are also highly variable in the population, with research showing that SAS-reducing bony morphologic variants exist even among a young healthy population (Chopp-Hurley, O’Neill, & Dickerson, 2016). As well, the multiple scapular muscle attachments vary across persons, creating variable force production capabilities (Chopp-Hurley et al, 2014; Picco et al, 2010).…”
Section: Muscular Fatigue As a Candidate Precipitator Of Occupational...mentioning
confidence: 99%
“…Small changes in SAS width can have important clinical implications. The occupation ratios of the combined thickness of subacromial tissue divided by the minimal SAS ranged from 21.6% to 108.9% (Chopp-Hurley, O’Neill, & Dickerson, 2016), indicating that even small changes to the width of the space should be considered. Conversely, Maenhout et al (2015) examined SAS width in overhead athletes using ultrasound and found increased SAS width following a fatigue protocol.…”
Section: Muscular Fatigue As a Candidate Precipitator Of Occupational...mentioning
confidence: 99%